A Model of intervention for the enhanced psychosocial skills development of children with autism enrolled in inclusive preschool settings - Alejandro, Melanie San Pablo
One of the principal objectives of this research was to verify the assumption of improvement in psychosocial skills of preschool-aged children with autism (CWA) who are enrolled in inclusive settings. To achieve this, an original assessment tool designed to measure degrees of psychosocial development was created, utilizing the subdomains of social development outlined in Toni Linder's Transdisciplinary Play-Based Assessment (TPBA) Model. The Scale of Psychosocial Skills, the assessment tool devised by the researcher, consisted of 70 descriptions of intrapersonal and interpersonal social skills which mothers and intervention specialists rated with reference to their child's/ward current levels of development. The scale was responded to by mothers and intervention specialists of CWA on two separate occasions, first, at the onset of the study and then next, a year later. Although all CWA subjects demonstrated significant improvement in all seven subdomains after a year in their current inclusive placement, greater improvements were notably manifest in some subdomains than others. Specifically, CWA demonstrated the greatest gains in Social Interactions with Peers, Mastery Motivation and Humor/ Social Conventions, according to rank. The next highest improvement ratings were noted for Social Interactions with Adults, Temperament, and Emotional Development while the least improvement was recorded for Social Interactions with Parents. The gains made in the different subdomains appeared to reflect the school culture of inclusion and its thrusts, policies and approaches utilized. From the data gathered, the researcher then proceeded to meet the ultimate objective of the study which was to formulate a relevant model of psychosocial intervention that would optimize resources and address weaknesses identified in current intervention models. For this phase of the study, the researcher utilized participant observation and an interview questionnaire in addition to conducting focus group discussions that tapped the expertise of general and special education teachers, other intervention providers, peers of CWA and CWA themselves in order to come up with a comprehensive and truly effective model of intervention. This new model describes an ideal therapeutic milieu for optimal progress of CWA, identifies stakeholders and their participation in the process, enumerates goals to be targeted in the different subdomains and outlines specific strategies to facilitate attainment of objectives. While there is still much to be done in the area of improving the lives of CWA, this study offers that elusive ray of hope to CWA and their families and strengthens one's faith in the good that a collective of concerned and enlightened individuals and agencies can achieve in their quest for the supreme expression and celebration of diversity.